2021
DOI: 10.1016/j.clnesp.2021.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Poor nutritional status, risk of sarcopenia and nutrition related complaints are prevalent in COVID-19 patients during and after hospital admission

Abstract: Clinicians should consider the risks of acute malnutrition and sarcopenia in COVID-19 patients and investigate multidisciplinary treatment including dietetics during hospital stay and after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 28 publications
6
100
1
4
Order By: Relevance
“…In our study, those patients who had high levels of inflammatory markers during COVID-19 had high FS. In a previous study, 35% of the hospitalised patients who suffered from COVID-19 was characterised as malnourished, mainly caused by considerable weight loss and 73% had high risk of sarcopenia ( 14 ). Immobility during hospital stay is further detrimental to skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, those patients who had high levels of inflammatory markers during COVID-19 had high FS. In a previous study, 35% of the hospitalised patients who suffered from COVID-19 was characterised as malnourished, mainly caused by considerable weight loss and 73% had high risk of sarcopenia ( 14 ). Immobility during hospital stay is further detrimental to skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Among these the following deficiencies were noted; 19.5% hypoalbuminemia, 19.5% hypocalcemia, 34.1% anemia, 12.2% hypomagnesemia and 51.2% deficiency in vitamin D(17). Despite these problems, nutrition advise has not been given adequately to the patients ( 14 ). In our study, those patients with T2D and previous COVID-19, and high FS, showed decreased serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although malnutrition and sarcopenia did not appear to be significant risk factors for the incidence of COVID-19 in the present study, the inverse relationship remains possible. Indeed, COVID-19 could be a risk factor for malnutrition due to its manifestation through gastrointestinal symptoms with nausea, vomiting, and loose bowel movement that could also cause anorexia [ 50 ]. In the same way, patients affected with COVID-19 have a decrease in their physical activity level because of isolation and fatigue, which can further accelerate the loss of muscle mass and strength and, therefore, engender sarcopenia [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, COVID-19 could be a risk factor for malnutrition due to its manifestation through gastrointestinal symptoms with nausea, vomiting, and loose bowel movement that could also cause anorexia [ 50 ]. In the same way, patients affected with COVID-19 have a decrease in their physical activity level because of isolation and fatigue, which can further accelerate the loss of muscle mass and strength and, therefore, engender sarcopenia [ 50 , 51 ]. Additionally, given their well-observed impact on the progression of COVID-19 with more extended hospitalization stays and a higher risk of mortality [ 52 55 ], these two clinical states still represent essential factors to be considered for better prevention and management of COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 114 patients with COVID-19 infection, COVID-19 patients with higher risk of sarcopenia as assessed by the SARC-F were demonstrated to be more likely to develop severe disease than those without (68% vs. 22%, p<0.001) (59). Of the 407 patients hospitalized with COVID-19, 22% had rapid weight loss during hospitalization and 73% had a SARC-F score of 4 or higher (60). In 152 patients with acute cerebral infarction, the SARC-F was reported to be useful in predicting functional outcome 3 months after stroke onset (61).…”
Section: Clinical Significance Of the Sarc-f According To Diseasesmentioning
confidence: 99%